A Study on the Correlation Between Higher Education Quality Assessment and Teacher Professional Development - Bingquan Jia; Wenhua Ma (Journal of Advanced Research in Education, 2023)
This article explores the correlation between higher education quality assessment and teacher professional development. Teachers are the most important resource and supporting force in higher education, and their professional abilities and development level directly affect students’ learning outcomes and educational quality. The quality assessment of higher education plays a guiding role in the professional development of teachers, while the professional development of teachers plays a guarantee role in the quality assessment of higher education. At the same time, there is a mutually promoting relationship between higher education quality assessment and teacher professional development, forming a virtuous cycle that jointly promotes the continuous improvement of higher education quality.